Development of Augmented Reality-Based Mobile Learning Media to Accommodate Learning Styles in Natural and Social Sciences Subjects: Pengembangan Media Mobile Learning Berbasis Augmented Reality Untuk Mengakomodasi Gaya Belajar pada Mata Pelajaran IPAS - Angel Vanessa Vanessa; Ahmad Ilham Asmaryadi; Wiwik Okta Susilawati (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This study aims to produce a valid, practical, and effective Augmented Reality (AR)-based mobile learning media, supported by Assemblr Edu, to accommodate Visual, Auditory, and Kinesthetic (VAK) learning styles for fourth-grade students at SDN 10 Sitiung. The research method used was Research and Development (R&D), with a 4-D development model encompassing the define, design, develop, and disseminate stages. The trial subjects were teachers and fourth-grade students at SDN 10 Sitiung, Dharmasraya Regency. The results showed that the Augmented Reality (AR)-based mobile learning media, supported by Assemblr Edu, achieved validation results from material experts of 86.6%, media experts of 97.5%, language experts of 96.6%, RPM experts of 100%, and question grids of 100%, which fall into the